Investigation on Gender and Learners-Centered Teaching Strategies Toward Learners' Writing Performance - Nursamsu Nursamsu (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
ABSTRACTThis research investigated the interaction effects between gender and Learner-Centered Teaching Strategies toward learners' writing performance. The study was a quasi-experiment using tests as the research instrument. The participants were 72 learners of the English Department at a state institution consisting of 34 males and 38 females. The class was classified into two parts: experiment groups consisting of self-directed learning class (SDL), discovery learning class (DL), and small group discussion class (SGD); and a control group: lecturing class (L). A two-way ANOVA was used for data analysis. The findings confirmed a significant difference by gender (F=10.629. Sig. 0.002<0.05); and Learner-Centered Teaching Strategies F=20.658. Sig. 0.000<0.050) on the learners' writing performance. It also indicated that females (means score 73.46) were higher than males (means score 64.45). In contrast, no interaction effect simultaneously occurred among gender and the Learner-Centered Teaching Strategies (F 2.70) = 2.301. Sig. 0.086>0.050). Both of them did not contribute simultaneously to writing performance. Lastly, the r squared was 0.574 indicating a high correlation of teaching strategies and gender (57%). The teachers were suggested to apply learner-centered teaching strategies in an L2 writing class at a higher education level.ABSTRAKPenelitian ini menyelidiki pengaruh interaksi antara gender dan strategi pengajaran terpusat pada peserta didik terhadap kinerja menulis peserta didik. Jenis penelitian ini adalah kuasi eksperimen dengan instrument yang digunakan adalah tes. Partisipan berjumlah 72 mahasiswa Jurusan Bahasa Inggris di sebuah universitas negeri yang terdiri dari 34 laki-laki dan 38 perempuan. Kelas diklasifikasikan menjadi dua bagian: kelompok eksperimen yang terdiri dari kelas self-directed learning (SDL), kelas discovery learning (DL), ; kelas diskusi kelompok kecil (SGD); dan kelompok kontrol: kelas kuliah (L). Anova dua jalur digunakan pada analisis data. Temuan mengkonfirmasi perbedaan yang signifikan terjadi untuk jenis kelamin (F = 10,629. Sig. 0,002 <0,05); dan strategi pengajaran terpusat pada peserta didik F=20.658. Sig. 0,000<0,050) terhadap kemampuan menulis siswa. Hal ini juga menunjukkan bahwa perempuan (rata-rata skor 73,46) lebih tinggi daripada laki-laki (rata-rata skor 64,45). Sebaliknya, tidak ada efek interaksi yang terjadi secara simultan antara gender dan strategi pengajaran terpusat pada peserta didik (F 2,70) = 2,301. Tanda tangan. 0,086>0,050). Keduanya tidak berkontribusi secara bersamaan pada kinerja menulis. Terakhir, nilai r kuadrat adalah 0,574 yang menunjukkan korelasi tinggi antara strategi pengajaran dan gender (57%). Para guru disarankan untuk menerapkan strategi pengajaran yang berpusat pada peserta didik di kelas menulis L2 di pendidikan tinggi.